2019
DOI: 10.1186/s12929-019-0540-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances on the role of host factors during non-poliovirus enteroviral infections

Abstract: Non-polio enteroviruses are emerging viruses known to cause outbreaks of polio-like infections in different parts of the world with several cases already reported in Asia Pacific, Europe and in United States of America. These outbreaks normally result in overstretching of health facilities as well as death in children under the age of five. Most of these infections are usually self-limiting except for the neurological complications associated with human enterovirus A 71 (EV-A71). The infection dynamics of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 196 publications
(184 reference statements)
0
23
0
Order By: Relevance
“…Immunopathological injury also affects the cardiopulmonary system [5] . There are yet no effective antiviral drugs targeting HFMD associated enteroviruses, although significant efforts have been made to understand virus-human host interactions in order to identify promising candidates [6] . The role of viral load in the progress of HFMD and development of complications is of significance to both clinicians and researchers alike.…”
Section: Introductionmentioning
confidence: 99%
“…Immunopathological injury also affects the cardiopulmonary system [5] . There are yet no effective antiviral drugs targeting HFMD associated enteroviruses, although significant efforts have been made to understand virus-human host interactions in order to identify promising candidates [6] . The role of viral load in the progress of HFMD and development of complications is of significance to both clinicians and researchers alike.…”
Section: Introductionmentioning
confidence: 99%
“…The strict compliance with nonpharmaceutical interventions implemented during the coronavirus disease (COVID-19) pandemic has been associated with a decline in influenza activity in many countries, including Taiwan (1)(2)(3)(4). Handwashing, disinfecting frequently touched surfaces, and closure of schools might also be effective against nonpolio enteroviruses (NPEV), which commonly cause a spectrum of illnesses in young populations in Asia (5). We observed lower NPEV activity during the 2019-20 season in Taiwan compared with the average of the 5 previous seasons, which might be attributable to strict compliance with nonpharmaceutical interventions.…”
mentioning
confidence: 99%
“…Another EV-A71 receptor called human P-selectin glycoprotein ligand-1 (PSGL-1) is expressed primarily on leukocytes and is bound by select EV-A71 strains . Additional attachment molecules that enhance viral infectivity and contribute to viral dissemination and neurotropism include heparan sulfate glycosaminoglycans (HS) (Tan et al, 2013), sialic acid (Yang et al, 2009), annexin II (Yang et al, 2011), nucleolin (Su et al, 2015), vimentin (Du et al, 2014) and heat shock protein 70 (Xu et al, 2019) among others (reviewed in Owino and Chu, 2019). Other receptors utilized by enteroviruses for cell entry that may contribute to neuropathogenicity include the decay-accelerating factor (DAF or CD55, part of the complement cascade) used by CVA21, echovirus 6 and echovirus 11 (Shafren et al, 1997;Lea et al, 1998;Renois et al, 2011) or Coxsackievirus and Adenovirus Receptor (CAR), which is the main entry receptor for Coxsackie B viruses (Martino et al, 2000).…”
Section: Receptors For Neurotropic Enterovirusesmentioning
confidence: 99%
“…Viral entry and replication rely heavily on numerous host factors and are fundamental processes dictating the success of a viral infection (Figure 1). Many studies have identified host factors that are critical for EV propagation (reviewed in Owino and Chu, 2019). However, much of this work was performed on nonneuronal cell types which have shown little overlap between the deregulated host proteins identified during EV infected motor neurons (Too et al, 2018), reinforcing the need to verify the role of these host factors in CNS relevant models.…”
Section: Host Factors Involved In Enterovirus Entry and Replicationmentioning
confidence: 99%